Review of the genus Cyrtopsis Bey-Bienko with a new species, a new combination and some new descriptions - Wang, Hanqiang; Qin, Yanyan; Liu, Xianwei; Li, Kai (Zootaxa, 2015)
This work involves a review of the genus Cyrtopsis, including description of 1 new species, Cyrtopsis furcicerca sp. nov., (originally considered as male and female variants of Cyrtopsis t-sigillata by Song et al. 2015) and a new combination, Cyrtopsis bivittata (Mu, He & Wang, 2000) comb. nov., based on males of the latter and Cyrtopsis t-sigillata. The other species of the genus are keyed and reviewed. Allspecimens are deposited in Shanghai Entomological Museum, Chinese Academy of Sciences, Shanghai, China (SEM, CAS).